PENGARUH TRANSAKSI ELECTRONIC BANKING TERHADAP FEE BASED INCOME PADA PT BANK CIMB NIAGA, Tbk PERIODE 2014 – 2017 - Oliviani Rizki Arisanti; Prihatiningsih Prihatiningsih (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2019)
This study aimed to knowing the effect of electronic banking transactions to fee based income PT. Bank CIMB Niaga, Tbk. The strategy that was used in this research was associative strategy or relations effect. The method was used in this research was ex post de facto. The subject in this research is PT. Bank CIMB Niaga, Tbk from the merger company that is between Bank Niaga with the Lippo Bank until now. Sample that was used is the e-banking transactions and fee based income of PT. Bank CIMB Niaga, Tbk for 4 years (year 2014-2017). The variable that was researched covered the free variable that is the e-banking transactions. Whereas the variable was tied was fee based income. This study was carried out by using the analysis technique of simple linear regression and for the data processing used spss the version 16,0. Were based on results of the testing of the hypothesis α = 5% df = n-k =2 was received t table is 4.302 and tcounted is 11,855 (t counted > t table) so the conclution H0 was refused and Ha was accepted, that means there is positive and significant influence the e-banking transactions to fee based income PT. Bank CIMB Niaga, Tbk.